EFEKTIVITAS MEDIASI DALAM PENYELESAIAN PERKARA PERCERAIAN DI PENGADILAN AGAMA PURWODADI - kunarto, kunarto; Prasetyo, Budi; Tsafitri, Della Ayu (PSHPM Untag Semarang, 2024)
Initially, mediation was part of an alternative dispute resolution method in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Mediation is considered an effective tool for resolving disputes quickly and cheaply and can provide parties with better access to finding satisfactory solutions. In this research, we examine the effectiveness of mediation in resolving divorce cases at the Purwodadi Religious Court. This research aims to determine the level of success of mediation at the Purwodadi Religious Court, the inhibiting factors and efforts to resolve it. This research uses a normative juridical type of research. The research used descriptive and qualitative research which took place at the Purwodadi Religious Court. Data taken in the field was collected using observation, interview and note-taking techniques. The collected data is then processed using data reduction analysis, data presentation and concluding. Based on the results of research regarding the effectiveness of mediation in divorce cases at the Purwodadi Religious Court, this is following Supreme Court Regulation (PERMA) Number 1 of 2016 concerning procedures for mediation in court. The mediator had difficulty reconciling the parties due to several factors and considered mediation to be ineffective. Inhibiting factors include the absence of one of the parties, the strong desire of the parties to divorce, family disputes that can no longer be maintained, psychological or mental factors of disappointment (psychiatric), lack of knowledge of mediation between the parties, community compliance, lack of intention. Good. Efforts to resolve these include: Providing guidance and counselling, the parties are active/open to resolving the case, providing counselling on the importance of mediation, the mediator's abilities, mediation facilities and electronic mediation.